A new species of Stenophragma Skuse from Borneo (Diptera: Mycetophilidae: Sciophilinae) - Bechev, Dimitar; Kazandzhieva, Svetlozara (Zootaxa, 2020)
Stenophragma borneense sp. n. from Borneo is described and illustrated. In the new species, a variability in the presence/absence and location of R4+5, including between left and right wings of the same specimen, is observed. The cell between Rs and R4+5, if present, can be triangular, trapeziform or almost squared. An identification key to the extant species of the genus is also provided.